2021
DOI: 10.1007/s13311-020-00981-9
|View full text |Cite
|
Sign up to set email alerts
|

What Animal Models Can Tell Us About Long-Term Psychiatric Symptoms in Sepsis Survivors: a Systematic Review

Abstract: Lower sepsis mortality rates imply that more patients are discharged from the hospital, but sepsis survivors often experience sequelae, such as functional disability, cognitive impairment, and psychiatric morbidity. Nevertheless, the mechanisms underlying these long-term disabilities are not fully understood. Considering the extensive use of animal models in the study of the pathogenesis of neuropsychiatric disorders, it seems adopting this approach to improve our knowledge of postseptic psychiatric symptoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 190 publications
(217 reference statements)
0
5
0
Order By: Relevance
“…At least in animal models, anxiety and depression are strongly associated events. ( 47 ) Chronic mild stress causes both anxiety and depression, is associated with long-term cognitive dysfunction, and potentiates the dysfunction observed in septic survivors. ( 48 , 49 ) It is believed that chronic stress and inflammation combine to compromise vascular and brain function.…”
Section: Discussionmentioning
confidence: 99%
“…At least in animal models, anxiety and depression are strongly associated events. ( 47 ) Chronic mild stress causes both anxiety and depression, is associated with long-term cognitive dysfunction, and potentiates the dysfunction observed in septic survivors. ( 48 , 49 ) It is believed that chronic stress and inflammation combine to compromise vascular and brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that microglia have a role in regulating mood and affective disorders, including depression, among the long-term mental health disorders found in sepsis survivors [ 5 , 133 ]. Recent work has demonstrated that microglia activation in the striatum is associated with increased firing of striatal medium spiny neurons and induces depressive-like behavior in mice.…”
Section: Molecular Mechanisms Of Neuronal Toxicity In Saementioning
confidence: 99%
“…The physiologic condition of sepsis is also initially characterized by a hyperinflammatory stage, as shown by the presence of fever, tachycardia, tachypnea, and altered leukocyte numbers along with a known site of infection ( 2 ). As with wound healing, neutrophil infiltration, in this case to the site of infection, is also required to clear pathogens and damaged tissue ( 3 ). Efferocytosis is also a key step in the septic response for eventual resolution and recovery ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%